Pengembangan E-Modul Interaktif Melalui Aplikasi Android Berbasis Guided Discovery Learning Pada Materi Hidrokarbon Untuk Kelas XI SMA/MA - Nadia Ardila; Suryelita Suryelita (Universitas Negeri Padang, 2023)
The material for hydrocarbons is quite dense but the allocation of study time at school is limited so that learning becomes less than optimal. Teaching materials are needed that can help students learn in class and independent learning outside of school. Technological developments allow teaching materials to be developed in electronic format. This teaching material can be used anywhere and anytime which is accessed via a mobile phone. In general, students already use Android, but it has not been widely used in learning. The teaching materials used in MAN 2 Kerinci are not yet scientific. Research was carried out with the aim of developing interactive e-modules through an android application based on guided discovery learning on hydrocarbon material for class XI SMA/MA and determining its validity and practicality. The type of research used is educational design research with a plomp development model. The instruments used in this study were validation and practicality questionnaires. The data obtained were then analyzed using the Aiken's V formula and the practicality percentage formula. Based on the research data, the validation test shows that the e-module is valid (0.83). The practicality test shows that the value of practicality for teachers and students is very practical (91% and 83%) in small groups.